Intervention pilot study: effects of breakfast oatdrink consumption on bowel function and health parameters among UTAR Kampar female university students - Quah, Hong Yi (2023)
Oat is claimed to promote several health benefits, which include promoting good bowel functions, promoting weight management, controlling blood glucose level, managing hypertension and reduce inflammation. However, there were contradictory results shown from the previous studies raises up the queries on how good actually the oat consumption on the bowel function and health parameters. Besides, there are lack of studies being out carried among the young adults from 18 – 25 years old and no studies related to this topic has been carried out in UTAR. Therefore, current study is aimed to investigate the effects of commercial oat drink (3 in 1) consumption on bowel function and general health among UTAR Kampar female university students. An intervention pilot study with a total of 26 participants was recruited and asked to consume a sachet of Quaker’s 3 in 1 instant oat drink during the 14-days of intervention. Questionnaire, bowel diary and food diary were used to collect the data. All the data collected were analyzed by using iii Microsoft Excel and SAS software. Chi-square test was used to test the discrete variables (bowel function) and paired T-test was used to test the continuous data (health parameters).Based on the results, our study gives an idea that oat drink consumption may relieve constipation, increase the risk of having diarrhea, better weight and glycemic management, increase blood pressure and no effects on the inflammation properties among UTAR Kampar female university students. Further studies which using large sample size, long duration and randomized controlled trial are suggested to be carried out to study the long-term effects of oat drink intervention on the bowel function and health parameters.